SINONIMITAS HADITS : Telaah Sinonim Term Hadits, Struktur, dan Macam Hadits - Robiatul Adawiyah; Romlah Abubakar Askar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2024)
Hadith have an important and fundamental role in the Islamic religion, namely as one of the guidelines and sources of Islamic law after the Koran. Hadith has many other terms which are known to be synonymous with the term hadith such as sunnah, khabar, and atsar. In this case there are several differences of opinion, some equate them and there are also those who differentiate these terms. Therefore, in the author's opinion, this is important to study in more depth. Thus, this article will discuss the synonymity of hadiths, as well as the overall structure and division of hadiths. The method used in writing this article is the library research method by collecting data from various types of existing literature related to the theme that the author is studying, both in the form of books, journals and other relevant literature.